High‐Ability Grouping: Benefits for Gifted Students' Achievement Development Without Costs in Academic Self‐Concept. Issue 4 (23rd November 2017) - Preckel, Franzis; Schmidt, Isabelle; Stumpf, Eva; Motschenbacher, Monika; Vogl, Katharina; Scherrer, Vsevolod; Schneider, Wolfgang
Abstract : Effects of full‐time ability grouping on students' academic self‐concept (ASC) and mathematics achievement were investigated in the first 3 years of secondary school (four waves of measurement; students' average age at first wave: 10.5 years). Students were primarily from middle and upper class families living in southern Germany. The study sample comprised 148 (60% male) students from 14 gifted classes and 148 (57% male) students from 25 regular classes (matched by propensity score matching). Data analyses involved multilevel and latent growth curve analyses. Findings revealed no evidence for contrast effects of class‐average achievement or assimilation effects of class type on students' ASC. ASC remained stable over time. Students in gifted classes showed higher achievement gains than students in regular classes.